INCOME ANALYSIS OF OIL PALM FARMERS IN IMPROVING THE ECONOMIC WELFARE OF FARMERS ISLAMIC ECONOMIC PERSPECTIVE IN LANGGA PAYUNG VILLAGE - siregar, ilfirayuarfika; Atika, Atika; Bi Rahman, Nur Ahmadi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This study aims to find out whether the income of oil palm farmers can meet the economic welfare of the family and to find out the fulfillment of the economic welfare of oil palm farmers in terms of income in Langga Payung Village. The research method used in this study is qualitative using the field research method. Field research is a research conducted in the field or at a research location to investigate the objective symptoms of what occurs in the location. The results of the study show that the income of oil palm farmers in Langga Payung Village is used to meet basic needs. Some farmers are looking for additional work because they feel that their income is lacking. From the perspective of Maqasid Syariah, it can be seen that the religious, physical, educational, and social needs of farmer families have been well met. Although most of the farming children do not continue their parents' palm oil business, they prefer to pursue higher education. Most farmers have also paid zakat or infaq from their income